Effects of Layer Nanodefects on the Light Transmission by Optical Elements with Multilayer Interference Coatings - Fekeshgazi, I.V.; Sidenko, T.S.; Mitsa, O.V.; Barna, P.; Kikineshi, O.E. (Ukrainian Journal of Physics, 2022)
The light transmission properties of optical elements with multilayer interference coatings (MLS) have been studied. The decreasing of transmittance maxima for optical elements with coating containing the defects is found to be stronger for larger refractive indices of the defect material. The shape of transmission curves substantially depends on the defect dimensions along the direction of light propagation and its arrangement in the layer bulk. The results obtained are necessary for the developing of a technology in fabrication of the optical elements with MLS as for the laser technique, as for the optical lenses.